Strategi Dalam Mengoptimalisasi Konten Di Tiktok Effa Design Dalam Upaya Meningkatkan Engagement Rate - Fadhilah, Syarifah; Nurjanah, Siti (Research and Community Service UNIVERSITAS KALBIS, 2024)
In the digital era, TikTok has become a vital tool for business promotion with over 1 billion active users. The